Implementasi Program Pendewasaan Usia Perkawinan Di Karang Taruna Manisa Kecamatan Baranti - Ramli, Rachmat; Hilal, Achmad; Rahmat, Rezqiqah Aulia; Syamsinar, A.; Saad, Rahmiyani; Lonik, Lorensius (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Teenage marriage can have an impact on both physical and biological aspects. Teenage pregnancy will be at greater risk of anemia and bleeding which will contribute to maternal and infant mortality rates. In terms of education, pregnant teenagers will lose the opportunity to continue their education to a higher level. The goal of PkM is the Maturation of Marriage Age to postpone the age of marriage to over 18 years, with an ideal age of 25 years for men and 21 years for women and stimulate creativity and apply interesting methods for target groups, create positive changes in the views and behavior of the younger generation, and build a more prosperous society by encouraging mature marriage. The method used in PkM activities is socialization and mentoring for the implementation of the marriage age maturity program in the Manisa youth organization, Baranti sub-district. The results of community service are that adolescent problems that occur in society have difficulty in handling early marriage. Communication built within the family is still very minimal. The conclusion of this activity is that the level of achievement of the output targets in this community service activity is in accordance with what was planned and the program that has been scheduled by the PkM TEAM.